Implementasi Computational Thinking dalam Mata Pelajaran PPKn SD dengan Menggunakan Media Puzzle - Khasyanah Jamillah (LPPM Universitas Terbuka, 2025)
This research aims to determine students' skills related to computational thinking skills, especially on the foundations of pattern recognition and abstraction in PPKn Pancasila subject material at SD Negeri Kwarasan. This study used qualitative research methods. Data collection techniques are carried out by means of observation and documentation. The data analysis used in this research is quantitative analysis. The subjects of this research were 18 class II students at SD Negeri Kwarasan. The results of the research show that students' skills in computational thinking are based on the foundations of pattern recognition and abstraction, indicating that there are still many students who have not yet completed computational thinking-based activities. This can be seen from the percentage achieved by no more than 80% of the activities carried out. In the activity of assembling the Garuda Pancasila puzzle, the percentage obtained by students was only 60%, while in the activity of telling pictures of the application of the Pancasila principles it was only 73%. However, class II students at SD Negeri Kwarasan like activities that integrate computational thinking skills, namely the activity of putting together puzzles.